Horseshoe Chaos in a Simple Memristive Circuit - Lei Wang; XiaoSong Yang; WenJie Hu; Quan Yuan (Journal of Applied Mathematics)
A simple memristive circuit model is revisited and the stability analysis is to be given. Furthermore, we resort to Poincaré section and Poincaré map technique and present rigorous computer-assisted verification of horseshoe chaos by virtue of topological horseshoe theory.